Genetic Risk for Recurrent Urinary Tract Infections in Humans: A Systematic Review. (30th March 2010) - Zaffanello, M.; Malerba, G.; Cataldi, L.; Antoniazzi, F.; Franchini, M.; Monti, E.; Fanos, V.
Abstract : Urinary tract infections (UTIs) are a frequent cause of morbidity in children and adults and affect up to 10% of children; its recurrence rate is estimated at 30–40%. UTI may occur in up to 50% of all women in their lifetimes and frequently require medication. Recent advances have suggested that a deregulation of candidate genes in humans may predispose patients to recurrent UTI. The identification of a genetic component of UTI recurrences will make it possible to diagnose at-risk adults and to predict genetic recurrences in their offspring. Six out of 14 genes investigated in humans may be associated with susceptibility to recurrent UTI in humans. In particular, the HSPA1B, CXCR1 & 2, TLR2, TLR4, TGF-β 1 genes seem to be associated with an alteration of the host response to UTIs at various levels.